Improved childhood immunization coverage using the World Health Organization's Tailoring Immunization Programmes guide (TIP) in a regional centre in Australia. Issue 1 (3rd January 2022) - Thomas, Susan; Durrheim, David; Islam, Fakhrul; Higgins, Helen; Cashman, Patrick
Abstract: In 2017 the World Health Organization's Tailoring Immunization Programmes guide (TIP) was used to identify pockets of low immunization coverage in Australia. The regional centre of Maitland had high numbers and rates of children who were overdue for scheduled vaccinations (2016, n = 344, 37.7%). Families were not opposed to immunization but had conflicting priorities or experienced service access barriers. A tailored strategy was developed including friendly, personalised reminders, outreach appointments and home visiting for those families most in need. Research translation was not quick and easy. A process evaluation identified areas where more support was needed to advance the strategy. Coverage rates have increased from 62.3% (2016) to 86.2% (2020). The number of overdue children has decreased even during COVID-19 restrictions when health services expected families would avoid primary care services. The TIP approach is valuable for improving childhood immunization coverage and is being utilised in other communities with low coverage.